Improvement of Work Facilities in the Wooden Batik Production Process in Krebet Peni Studio to Minimize Muscoloskeletal Disorders (MSDs) - Davis Achriyandi Hisyammudin; Aayudyah Eka Apsari (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
The production process of wooden batik at Sanggar Peni Krebet plays an important role in preserving local culture and supporting the economy, but workers face the risk of musculoskeletal disorders due to unergonomic working positions when performing activities such as sculpting, sanding, batik making, and boiling . Based on the NBM questionnaire on 15 workers, the highest complaints were found in the right upper arm (100%), right wrist (100%), and waist (88%). Research using the RULA and REBA methods revealed the batik activity to have a very high risk (RULA 7, REBA 11), requiring immediate improvement, while boiling had a medium to high risk (RULA 5, REBA 9), requiring investigation and change. The EFD emphasizes the importance of designing batik boiling stoves, chairs and tables that consider height according to the worker's body size, ergonomic working positions, and comfortable strainer handles. Tool development should focus on improving comfort, safety and efficiency, with design adjustments to support workers' postures and use lightweight yet strong materials. The application of these elements is expected to improve safety and productivity in the batik industry.